2001
DOI: 10.1007/s100530170089
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron radiation studies of mass-selected Fe nanoclusters deposited in situ

Abstract: A portable UHV-compatible gas aggregation cluster source, capable of depositing clean massselected nanoclusters in situ, has been used at synchrotron radiation facilities to study the magnetic behaviour of exposed and Co-coated Fe clusters in the size range 250 to 540 atoms. X-ray magnetic circular dichroism (XMCD) studies of isolated and exposed 250-atom clusters show a 10% enhancement in the spin magnetic moment and a 75% enhancement in the orbital magnetic moment relative to bulk Fe. The spin moment monoton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Such experiments have been carried out by Gambardella et al [5,6] who have indeed measured orbital moments as large as 0.68µ B for Co chains on Pt(997) and 1.1µ B for a Co adatom on Pt(111), the corresponding MAE being 2meV and 9meV per Co atom, respectively. Moreover XMCD experiments carried out on iron clusters [7,8] have shown that the orbital moment is much more enhanced than the spin moment as the size is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Such experiments have been carried out by Gambardella et al [5,6] who have indeed measured orbital moments as large as 0.68µ B for Co chains on Pt(997) and 1.1µ B for a Co adatom on Pt(111), the corresponding MAE being 2meV and 9meV per Co atom, respectively. Moreover XMCD experiments carried out on iron clusters [7,8] have shown that the orbital moment is much more enhanced than the spin moment as the size is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…An example of mass spectra obtained at two different pressures is shown in figure 1, which also displays an in situ STM image obtained in a previous study of unfiltered Fe clusters deposited on Si(111) under similar preparation conditions. It has been verified that, in the case of Fe clusters, the mass distribution measured in the free cluster beam is unchanged after depositing on a substrate [18] or embedding in a matrix [11]. The mass spectra show the expected log-normal shape and the curves in figure 1 are optimized fits as a function of the mean size ( n ) and the standard deviation (σ ).…”
Section: Preparation Of Cluster Filmsmentioning
confidence: 79%
“…1,2 Owing to the fact that a major factor controlling the OMM is the spin-orbit (SO) interaction, 24 considerable efforts have been devoted to producing nanograins made of magnetic materials with large magnetic moments, large SO coupling, and large magnetic anisotropy energy. [3][4][5][6][7][8][9][10][11][12][13] Thus, investigations of magnetic nanograins consisting of elemental or binary clusters based primarily on the TM atoms such as Co, Fe, and Ni have been attempted. In the case of binary grains the second material can be a metal (TM, Cu, Ag, Au), a semiconductor (C, Si), or a rare earth (Sm).…”
mentioning
confidence: 99%